A critical review of Oscar Niemeyer’s Design Process - Hiroki, Juliana Eiko; Rozestraten, Artur Simões (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
The new technologies of today's world, applied in the perceptive and creative processes, bring the need to rediscover the role of representations in both, academic and professional, areas of architecture. Therefore, this article seeks to understand and demystify Oscar Niemeyer’s (1907-2012) design process, one of the most renowned Latin American architects in the world and known for his peculiar design process - distinguished by consisting only of sketches and texts, but, as this research reveals, also by physical models - and his broad professional activity, which accompanied the variations occurred in architectural production in Brazil and in the world, between the years 1940 and 2010